Application of biotechnology in agriculture: a bioinformatic and market analysis of novel intervention methods - Frazier, Anthony Nathan, author; Yang, Hua, advisor; Metcalf, Jessica, advisor; Martin, Jennifer, committee member; Leach, Jan, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Keywords: calf scours; Listeria spp.; microbiome; CRISPR-Cas9; bovine respiratory disease; market research